Orthopaedic Injuries in Equestrian Sports: A Current Concepts Review - Young, Jason David; Gelbs, Jared Craig; Zhu, David Shiyu; Gallacher, Stacey Elisa; Sutton, Karen Michelle; Blaine, Theodore Alton (Orthopaedic Journal of Sports Medicine, 2015)
Background: Despite the common nature of orthopaedic injuries in equestrian sports, there is no published review to specifically characterize orthopaedic injuries in equestrian athletes. Purpose: To characterize orthopaedic injury patterns in equine sports–related injuries and their treatment. Study Design: Systematic review; Level of evidence, 4. Methods: This review was performed through a PubMed, EMBASE, and Scopus query (from 1978 to June 2014) in the English literature using search terms “(equine-related OR equestrian-related OR horse-related OR equestrian OR equestrians) AND (injury OR injuries).” Only full-text studies reporting on orthopaedic injury patterns pertinent to equestrian sports in the United States (US) and the United Kingdom (UK) were included. Orthopaedic injuries were defined as those resulting in a fracture or dislocation. In all, 182 studies were excluded, leaving a total of 27 studies for evaluation. The studies included were analyzed for demographic and epidemiological data for orthopaedic injuries, including fractures and dislocations. Cranial and facial injuries were excluded from analysis. Results: The majority of those injured in the US were female (64.5%). The leading cause of injury in the US was falling from a horse. The use of protective equipment seemed to vary widely, with helmet use ranging from less than 6% up to 66.7%. In the UK, fractures were found to account for 17.4% of reported injures, compared with 33.6% of injuries in the US. The majority of fractures in US riders occurred in the upper extremities (50.7%). Conclusion: This review helps characterize the epidemiology of equestrian injuries based on currently available data.